PELAYANAN ADMINISTRASI TERPADU KECAMATAN DALAM MEWUJUDKAN INOVASI DAN TATAKELOLA PEMERINTAHAN YANG BAIK (GOOD GOVERNANCE) DI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Monalisa, Monalisa (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
The Importance of Implementation of the District Integrated Administrative Service (PATENT) is an effort to realize the District as a service center, both Administrative Services Licensing and Non Licensing as well as a service node for the Integrated Service Agency in the county. The licensing services provided by the District Bangko Pusako them is licensing the restaurant business. PATENT held in District Bangko Pusako with the purpose of licensing administration service closer to the community, especially for house clearance meal and increase investment and local revenue. Whether or not the purpose of the granting of licenses will be determined by the procedure in specified districts. This is a challenge and an opportunity for the State Civil Apparatus as providers of services to the community in the globalization era full of challenges, namely how to seek to provide the best service towards good governance. With the granting of permits expected by society to get services more quickly, easily and accountable. The easier, faster, and more transparent permit granting procedures, then the quality of service diberikan.Tujuan study is to determine the sub-district administrative services integrated in the management of the restaurant business license in the District Office Bangko Pusako Rokan Hilir. The method used is qualitative descriptive type. The process of data analysis is done by reviewing all available data from interviews, observations, and read the documents until the conclusion. The results showed that the public as users of services was not satisfied with the services provided. Especially in terms of the requirements that still burden the people, the service time is less precise and lack of transparency in the cost of services provided. Having analyzed knowable inhibiting the delivery of services the restaurant business license is not effective determination of the conditions of service and there is no commitment from all personnel in the district to organize PATENT into a better direction. Based on the research and analysis it can be concluded that the provision of services on the restaurant business license in the District Office Bangko Pusako Rokan Hilir has not run optimally and still needs to be improved quality of service.